Hoc quod uolo / me nolle: Counter-Volition and Identity Management in Senecan Tragedy - Gottfried Mader (Pallas, 2014)
Akrasia and involuntary action are conspicuous in several Senecan tragedies, where pivotal moments are minutely dramatized as crises of will, and where protagonists under massive duress (internal or external) act self-consciously against their better judgment (Herc. F., Phoen., Pha., Med., Thy.). These counter-volitional psychodramas, a species of the Senecan Affektszene, play out according to a typical pattern that includes the following elements: competing impulses (often signalled by cogere, invitus, nolle/uelle, ducere/sequi), acute self-awareness, self-directed commands, the impossible choice, akratic immobility, fragmentation of personality; and in every case, failure of will doubles as a crisis of identity, with the impasse only broken when in a psycho-cybernetic process the subject consciously affirms (or is coerced to affirm) a particular version of the self. Five scenes, all separately recognized as crucial in their own right, are here analysed within the counter-volitional matrix; the clinical gaze of the philosopher conjoins with a baroque tendency towards excessive detail, pathos and violence to produce a distinct subset of the literary psychodrama.